2007
DOI: 10.1007/s10549-006-9456-9
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 genetic testing in 106 breast and ovarian cancer families from southern Italy (Sicily): a mutation analyses

Abstract: The present study is the first BRCA1 disease-associated mutations analysis in Southern Italian families. The early age of onset of such tumors and the association with the HBOC familial profile could be two valid screening factors for the identification of BRCA1 mutation carriers. Finally, we identified a BRCA1 mutation with a possible founder effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 44 publications
4
22
0
Order By: Relevance
“…The detection rate comparable to ours was reported in the Sicilian population 16% [26], or in Spain 17.1% [27].…”
Section: Other Hboc Risk Genes -Tp53 Chek2*1100delc Analysissupporting
confidence: 90%
See 3 more Smart Citations
“…The detection rate comparable to ours was reported in the Sicilian population 16% [26], or in Spain 17.1% [27].…”
Section: Other Hboc Risk Genes -Tp53 Chek2*1100delc Analysissupporting
confidence: 90%
“…The lowest rate of only 10% was present in families with unilateral breast cancer. According to the reported data and also comparing with other studies [25,26,28,29], the presence of ovarian cancer in association with breast cancer serves as a potential predictive factor for BRCA1 mutation positivity and represents the strongest indication. On the other hand, the presence of bilateral ovarian (17%) or breast (13%) cancer is still stronger criterion for selection as the familiar unilateral cancer.…”
Section: Other Hboc Risk Genes -Tp53 Chek2*1100delc Analysismentioning
confidence: 66%
See 2 more Smart Citations
“…Mutations in the RING finger domain were detected in breast cancer patients from Chile, Japan and India (25)(26)(27), and several large studies in Italy and Germany (6,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) showed polymorphisms and mutations in this region in patients but also in the control population. However, consistent with the conserved status of the region, we did not detect any variants of the RING finger domain in the healthy Croatian population.…”
Section: Distribution Of Variants Across the Protein Domainsmentioning
confidence: 99%